Integrating site-specific environmental impact assessment in supplier selection: exemplary application to steel procurement - Andreas Schiessl; Richard Müller; Rebekka Volk; Konrad Zimmer; Patrick Breun; Frank Schultmann (Journal of Business Economics, 2020)
In times of fast-growing stakeholder interest in sustainability, the ecological and social perspective of industrial companies and its products is gaining increasing importance. In particular, the emission of greenhouse gases (GHG) in the automotive industry has come to the forefront of public and governmental attention. The transport sector accounts for 27% of all European GHG emissions and constitutes the largest emitter of CO2e (CO2 equivalents) among all energy demanding technologies. Due to increasingly efficient combustion engines and technology innovation towards e-mobility, the emissions from car manufacturing gain in importance. So far little focus has been laid upon the emissions created throughout the production process in automotive supply chains from a purchasing perspective. The purchasing of raw material from environmentally efficient suppliers can constitute a possibility to significantly reduce CO2e emissions in automotive supply chains and thus contribute to the two degrees global warming goal. Supplier selection decisions, which cover approximately 75% of the value adding process of a car, are today mainly cost and quality-driven. In order to integrate CO2e as decision criterion for supplier selections, site-specific and comparable data on CO2e emissions from the upstream supply chain is necessary, but currently lacking. To estimate CO2e emissions of steel suppliers' production sites, a model has been developed to estimate manufacturing processes on a site-specific level without the necessity of confidential primary data. The model is applied on 22 integrated steel mills in EU-15. The results, which can be transferred and used for various products and industries, e.g. the construction industry, demonstrate the partially large disparities of manufacturing efficiency regarding CO2e emissions among steel manufacturers due to different levels of process integration and internal process know-how. A range between 1879 and 2990 (kg CO2e/t crude steel) has been revealed. Finally, the estimated data on CO2e performance of suppliers is applied in a case study of supplier selection of a German automobile manufacturer in order to simulate environmental as well as economic effects.
Keywords: Q50; Q51; Q54; Q55; Q56; L61; L62; 650; LCA; CO2e; Carbon footprint; Iron-and steel industry; Product assessment; Credit system; Decision making; Supplier selection; Automotive industry